Association between a rare novel TP53 variant (rs78378222) and melanoma, squamous cell carcinoma of head and neck and lung cancer susceptibility in non‐Hispanic Whites. Issue 7 (7th June 2013) - Guan, Xiaoxiang; Wang, Li‐E; Liu, Zhensheng; Sturgis, Erich M; Wei, Qingyi
Abstract: Recently, several studies have investigated the association between a newly reported rare functional single nucleotide polymorphism (SNP) in TP53 (rs78378222) and cancer risk, but generated inconsistent findings. The present study further investigated this association with risk of melanoma, squamous cell carcinoma of head and neck (SCCHN) and lung cancer. Using volunteers of non‐Hispanic Whites recruited for three large case–control studies, we genotyped the TP53 rs78378222 SNP in 1329 patients with melanoma, 1096 with SCCHN, 1013 with lung cancer and 3000 cancer‐free controls. Overall, we did not observe any variant homozygotes in this study population, nor significant associations between the TP53 rs78378222AC genotype or C allele and risk for melanoma ( P = 0.680 and 0.682 respectively) and lung cancer ( P = 0.379 and 0.382 respectively), but a protection against SCCHN ( P = 0.008 and 0.008 respectively), compared with the AA genotype or A allele. An additional meta‐analysis including 19, 423 cancer patients and 54, 050 controls did not support such a risk association either. Our studies did not provide statistical evidence of an association between this rare TP53 variant and increased risk of melanoma, nor of lung cancer, but a possible protection against SCCHN.